Evolution of the Definition of Bronchopulmonary Dysplasia and Its Long-Term Outcomes - Jeon, Ga Won (Perinatology (Online), 2024)
Bronchopulmonary dysplasia (BPD) remains a significant concern in neonatal care despite advancements in intensive care for preterm infants, as its incidence continues to rise. This chronic complication of prematurity not only affects respiratory function but also has impacts on growth and neurodevelopment into childhood and adolescence. The evolution of BPD definitions reflects the changing landscape of neonatal care, aiming to better predict long-term outcomes and guide early interventions. While the National Institute of Child Health and Human Development (NICHD) 2001 definition set a standard for classifying BPD severity, its limitations in capturing diverse respiratory support and predicting long-term outcomes have prompted the development of newer definitions, such as the NICHD 2018 and Neonatal Research Network 2019 definitions. These updated definitions offer improvements by considering a broader range of respiratory support criteria and enhancing predictive value for mortality, respiratory morbidity, growth, and neurodevelopmental impairment. The primary goal of defining BPD and grading its severity is to identify high-risk infants early, enabling targeted interventions to improve long-term outcomes. Future efforts should focus on refining BPD definitions to best predict these outcomes and optimize care for this vulnerable population. KCI Citation Count: 0